A homozygous founder mutation in associates with a neurodevelopmental disorder characterised by microcephaly, epilepsy and autistic features. - Marin-Valencia, Isaac; Novarino, Gaia; Johansen, Anide; Rosti, Basak; Issa, Mahmoud Y; Musaev, Damir; Bhat, Gifty; Scott, Eric; Silhavy, Jennifer L; Stanley, Valentina; Rosti, Rasim O; Gleeson, Jeremy W; et al. (J Med Genet, 2018)
BACKGROUND: Transport protein particle (TRAPP) is a multisubunit complex that regulates membrane trafficking through the Golgi apparatus. The clinical phenotype associated with mutations in various TRAPP subunits has allowed elucidation of their functions in specific tissues. The role of some subunits in human disease, however, has not been fully established, and their functions remain uncertain. OBJECTIVE: We aimed to expand the range of neurodevelopmental disorders associated with mutations in TRAPP subunits by exome sequencing of consanguineous families. METHODS: Linkage and homozygosity mapping and candidate gene analysis were used to identify homozygous mutations in families. Patient fibroblasts were used to study splicing defect and zebrafish to model the disease. RESULTS: We identified six individuals from three unrelated families with a founder homozygous splice mutation in , encoding a core subunit of the complex TRAPP I. Patients manifested a neurodevelopmental disorder characterised by microcephaly, epilepsy and autistic features, and showed splicing defect. Zebrafish morphants replicated the human phenotype, displaying decreased head size and neuronal hyperexcitability, leading to a lower seizure threshold. CONCLUSION: This study provides clinical and functional evidence of the role of in brain development and function.
Keywords: Animals; Autistic Disorder; Epilepsy; Founder Effect; Genetic Association Studies; Homozygote; Humans; Microcephaly; Mutation; Neurodevelopmental Disorders; Phenotype; Vesicular Transport Proteins; Zebrafish

Homozygous Mutations in TBC1D23 Lead to a Non-degenerative Form of Pontocerebellar Hypoplasia. - Marin-Valencia, Isaac; Gerondopoulos, Andreas; Zaki, Maha S; Ben-Omran, Tawfeg; Almureikhi, Mariam; Demir, Ercan; Guemez-Gamboa, Alicia; Gregor, Anne; Issa, Mahmoud Y; Appelhof, Bart; Roosing, Susanne; Musaev, Damir; et al. (Am J Hum Genet, 2017)
Pontocerebellar hypoplasia (PCH) represents a group of recessive developmental disorders characterized by impaired growth of the pons and cerebellum, which frequently follows a degenerative course. Currently, there are 10 partially overlapping clinical subtypes and 13 genes known mutated in PCH. Here, we report biallelic TBC1D23 mutations in six individuals from four unrelated families manifesting a non-degenerative form of PCH. In addition to reduced volume of pons and cerebellum, affected individuals had microcephaly, psychomotor delay, and ataxia. In zebrafish, tbc1d23 morphants replicated the human phenotype showing hindbrain volume loss. TBC1D23 localized at the trans-Golgi and was regulated by the small GTPases Arl1 and Arl8, suggesting a role in trans-Golgi membrane trafficking. Altogether, this study provides a causative link between TBC1D23 mutations and PCH and suggests a less severe clinical course than other PCH subtypes.
Keywords: Adolescent; Animals; Cerebellar Diseases; Child; Child, Preschool; Female; GTPase-Activating Proteins; HeLa Cells; Homozygote; Humans; Male; Microcephaly; Mutation; Pedigree; Phenotype; Zebrafish